Gender and the political economy of land in Africa - Kouamé, Euphrasie B.H.; Fofona, Namizata B. (United Nations University Institute for Natural Resources in Africa, 2015)
Evidence shows that secure land rights have positive effects on poor people in general and women in particular, especially where households previously had little security. Several countries in Africa have been undertaking land reform initiatives that prohibit gender-based discrimination; however, the results revealed a substantial gap between the development of laws and their effective implementation. This paper draws attention to the political systems within which land tenure and property rights operate, especially for women. It also points out the main challenges in securing women’s land rights in Africa and highlights the economic, social and environmental benefits of increasing women’s access to land. The analysis shows that although many of the changes in policy and law appear to be legal and technical, access to and control over land is in practice related to socio-economic characteristics and governed by cultural practices and power relations at the family, community and country levels. The paper therefore recognizes the need for innovative approaches that go beyond property rights in operationalising strategies that strengthen women’s access to land. It is not enough for land legislation to be gender-sensitive; it must be gender-transformational. Land markets could potentially contribute to this transformation but their role is still limited by poor institutional capacity. The roles that different actors (women, men, women’s organizations, community leaders, donors) can play would be crucial in the process of securing women’s access to land in Africa.
ISBN: 9789988633066
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; afrique; approches et analyses; femmes*; genre; identités LGBTQIA2+; politique; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; thématiques; égalité des sexes

Le genre dans la communication et les médias: enjeux et perspectives - Julliard, Virginie; Quemener, Nelly (Revue française des sciences de l’information et de la communication, 2014)
Des débats sur la parité aux émissions de relooking, en passant par les sites de rencontre ou encore la publicité, il semble aujourd’hui difficile d’analyser les objets de prédilection des sciences de l’information et de la communication sans interroger les rapports sociaux de genre qui les structurent. Que l’on s’intéresse aux pratiques, aux dispositifs, aux représentations ou aux discours médiatiques, il ne s’agit pas seulement d’appréhender le genre à la façon d’un nouvel objet de recherche mais bien de le considérer comme une perspective à part entière. Les travaux qui se sont penchés ces dernières années sur les campagnes présidentielles de 2007 et 2012 ont par exemple démontré le caractère heuristique d’une démarche communicationnelle au prisme du genre. Comment en effet comprendre la couverture médiatique des duels des présidentiables Sarkozy/Royal et Sarkozy/Hollande ou la stratégie de communication de la présidente du Front National Marine Le Pen sans prendre en considération la mise en scène des masculinités et féminités des personnalités concernées ? Surtout peut-on ignorer les rapports de pouvoir dans lesquels s’inscrivent de telles mises en scène et les phénomènes de (dis)qualification qui découlent de ces dernières ?
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; approches et analyses; com5170; communication; cours; discipline; europe; france; genre; histoire et politique; médias; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; thématiques